(untitled) (Research, Society and Development, 2023)
The study addresses the description of a clinical case of a male patient, 26 years old, who had an erupted upper right third molar. The patient sought treatment at the Faculdade Integrada Carajás clinic due to the discomfort and pain he was feeling. After clinical and imaging examinations, including panoramic radiography, the extraction of tooth 18 was indicated due to the presence of a carious lesion and gingival inflammation. Within the procedure by extraction through the alveolar route, using straight and lateral Seldin extractors, as well as the 18 R forceps. This less traumatic approach provided satisfactory results, emphasizing the importance of adequate clinical and auxiliary examinations by the dental surgeon.